1995
DOI: 10.1021/jo00126a040
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 1-alkoxy- and 1-(benzyloxy)-9,10-anthraquinones in methanol: A facile process for the preparation of aldehydes and ketones

Abstract: The facile production of acid sensitive aldehydes and ketones via photochemical intramolecular &hydrogen atom transfer in 1-alkoxy-and l-(benzyloxy)-9,10-anthraquinones (1) was investigated. Irradiation of 1 in argon purged methanol generates the primary photoproducts, l-(RCH(OMe)O)-and l-(ArCH(OMe)O)-9,1O-anthrahydroquinones (2), respectively. Upon exposure to air, the intermediate anthrahydroquinone is rapidly converted to the corresponding aldehyde and l-hydroxy-9,lO-anthraquinone (3), which can be recycled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 1 publication
2
24
0
Order By: Relevance
“…Blankespoor et al have shown that irradiation of 1-alkoxy and 1-benzyloxy-9,10anthraquinones in polar solution and in the presence of oxygen results in the formation of the corresponding 1-hydroxyanthraquinone together with a carbonyl compound, and that this reaction is useful for the synthesis of aldehydes and ketones on a preparative scale. 78,79 The proposed mechanism, as illustrated in Scheme 7, formally represents an intramolecular redox reaction between the anthraquinone moiety and the 1-alkoxy substituent. In the first step of the reaction, photolysis at 350 nm (e.g.…”
Section: Light-induced Release Of Volatile Carbonyl Compounds And/or ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Blankespoor et al have shown that irradiation of 1-alkoxy and 1-benzyloxy-9,10anthraquinones in polar solution and in the presence of oxygen results in the formation of the corresponding 1-hydroxyanthraquinone together with a carbonyl compound, and that this reaction is useful for the synthesis of aldehydes and ketones on a preparative scale. 78,79 The proposed mechanism, as illustrated in Scheme 7, formally represents an intramolecular redox reaction between the anthraquinone moiety and the 1-alkoxy substituent. In the first step of the reaction, photolysis at 350 nm (e.g.…”
Section: Light-induced Release Of Volatile Carbonyl Compounds And/or ...mentioning
confidence: 99%
“…Then an intramolecular electron transfer gives rise to a zwitterion, which can react with the solvent to form an anthrahydroquinone intermediate, which is eventually oxidised when exposed to air to give 1-hydroxyanthraquinone and the desired carbonyl compound. 78 The rate of the reaction is influenced by the size of the alkyl substituent at the 2-position of the anthraquinone moiety (R 3 in Scheme 7) and can be increased by a factor of ten moving from the smallest (R 3 = H) to the largest (R 3 = benzyl) of the groups tested. 78 Brinson and Jones showed that 1-alkoxy-9,10-anthraquinones also allow the photochemical generation of α,β-unsaturated aldehydes and reported the release of bioactive trans-4-hydroxy-2nonenal from precursor 21 (Fig.…”
Section: Light-induced Release Of Volatile Carbonyl Compounds And/or ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The photoreactions were examined in the presence or absence of O 2 . Mechanistically, 1,5‐biradical 102 , formed by an intramolecular 1,6‐hydrogen abstraction, collapses into zwitterion 103 via intramolecular electron transfer ,. Capture of 103 by methanol gives hydroquinone 104 as the primary product, ( 1 H NMR analysis).…”
Section: Photooxidation Of Anthraquinonesmentioning
confidence: 99%
“…An additional kinetic study revealed the influence of the size of the C2 substituent. For example, a substrate without the C2 methyl group underwent demethylation much slower than 101 , showing again the importance of buttressing effect to place the O ‐methyl group close to the photoexcited carbonyl for the 1,6‐hydrogen abstraction, (see also Baldwin's example, Scheme ).…”
Section: Photooxidation Of Anthraquinonesmentioning
confidence: 99%